Effect of Different Parameters on Mechanical and Erosion Wear Behavior of Bamboo Fiber Reinforced Epoxy Composites - Anu Gupta; Ajit Kumar; Amar Patnaik; Sandhyarani Biswas (International Journal of Polymer Science)
The application of natural fibers as reinforcement in polymer composites has been continuously growing during the last few decades. These composites find diverse applications in hostile environment where they are exposed to external attacks such as solid particle erosion. Also, in many respects, the mechanical properties of different polymer composites are their most important characteristics. Therefore, improvement of the erosion resistance and mechanical behavior of polymer composites are the prime requirements in their applications. Bamboo fiber which is rich in cellulose, relatively inexpensive, and abundantly available has the potential for reinforcement in polymers. To this end, an attempt has been made in this paper not only to study the utilization potential of bamboo fiber in polymer composites but also to study the effect of various parameters on mechanical and erosion wear performance of bamboo fiber reinforced epoxy composites.